FAKTOR YANG MEMPENGARUHI BELAJAR WARGA BELAJAR PENDIDIKAN PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) BINA KREASI KELURAHAN TANGKERANG TIMUR KECAMATAN TENAYAN RAYA - Oktaviani, Rani; Maemunaty, Titi; Widiastuti, Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Research it is based on research by a factor that affect learn residents learning package c in education Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kelurahan Tangkerang Timur Kecamatan Tenayan Raya. Because of factors affect learn a resident of learning education part of the package C to Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kelurahan Tangkerang Timur Kecamatan Tenayan Raya is a condition or event that affects a person to obtain good science. The formulation of a problem of this research is will a factor that is dominant among the internal factor to external that affects learning education residents package C in Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kelurahan Tangkerang timur Kecamatan Tenayan Raya?. The purpose of this research is to find out which factors other than a fuel that are more dominant of the civil servants some strong consumption and export growth to external that affects learn a resident of education a key insight about learning registration to join package C in Pusat Kegiatan Belajar Masyarakat (PKBM) Bina Kreasi Kelurahan Tangkerang timur Kecamatan Tenayan Raya. Population in this research as many as 57 people are residents of learning . Then the researcher determine samples from 35 people for research and 20 people for testing , by the use of sampling jenuh. An instrument to only 75 such data collection that is a statement and if the trial live 69 a statement that valid for research in made instrument . The analysis of data descriptive quantitative analysis . So factors the highest of the internal and external factors that affects learning education residents package C is the external factor.Key words: Factor, Factors learn residents learn education package C